La place des archontes dans la vie socio-politique de la cité de Synnada en Phrygie pendant l’époque romaine - Baldé, Sana (Res antiquae, 2022)
The city of Synnada in Phrygia, which is said to have been elevated to the rank of a city from the 2nd century BC, had, apart from an Assembly of the people and a Council, several colleges of magistrates who were responsible for carrying out current affairs. This study, constituting a contribution to the political-institutional history of the Greek cities of Asia Minor, analyses the role of the college of archons in the city of Synnada, particularly during the Roman period.